Promoting sulfidation of smithsonite by zinc sulfide species increase with addition of ammonium chloride and its effect on flotation performance. (15th August 2018) - Bai, Shaojun; Li, Chunlong; Fu, Xianyu; Ding, Zhen; Wen, Shuming
Graphical abstract: Highlights: The addition of NH4 Cl promoted sulfidation of smithsonite and improved its flotation performance with sodium isoamylxanthate. The thickness of formed zinc sulfide species and xanthogenate on samples was firstly determined by TOF-SIMS analysis. More zinc sulfide species were produced on the surface of smithsonite in the presence of NH4 Cl. The zinc sulfide species were derived from ion-exchange reaction product and sphalerite precipitation adsorption. Abstract: The sulfidation-flotation method is commonly used for the treatment of zinc oxide minerals. However, few studies have been conducted on the promoting sulfidation-flotation behavior and mechanism of smithsonite. In this paper, we investigate the promoting sulfidation of smithsonite by zinc sulfide species increase with addition of ammonium chloride (NH4 Cl) and its effect on flotation performance. The micro-flotation experiment results concluded that the addition of the ammonium chloride improved smithsonite flotation recovery by ∼17%. Zinc ion adsorption experiments and Visual MINTEQ model analysis showed that more zinc sulfide species were produced in the presence of NH4 Cl. Zeta potential analysis indicated that additional sulfide ion species and isoamyl xanthate ions (IX − ) from the pulp solution adhered to the smithsonite surface as NH4 Cl was added, and the SEM-EDS study and the contact angle results further confirmed the positive influence of NH4 Cl on the smithsonite sulfidation process. The TOF-SIMS results provided strong evidence for an increase in zinc sulfide species on the smithsonite surface and an increase in the sodium isoamyl xanthate (NaIX) molecular adsorption on the surface of sulfidized smithsonite with the addition of NH4 Cl. The thickness of zinc sulfide species formed after promoting sulfidation was ∼29.20 nm, and the thickness of xanthogenate species formed was a few nanometers. The promotion in sulfidation may be due to the combined effect of the improvement of sphalerite precipitation adsorption and the ion-exchange reaction between the sulfide ions and the carbonate ions on the surface of the smithsonite.